X+(12-x)*(12-x)=80

Simple and best practice solution for X+(12-x)*(12-x)=80 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for X+(12-x)*(12-x)=80 equation:



X+(12-X)(12-X)=80
We move all terms to the left:
X+(12-X)(12-X)-(80)=0
We add all the numbers together, and all the variables
X+(-1X+12)(-1X+12)-80=0
We multiply parentheses ..
(+X^2-12X-12X+144)+X-80=0
We get rid of parentheses
X^2-12X-12X+X+144-80=0
We add all the numbers together, and all the variables
X^2-23X+64=0
a = 1; b = -23; c = +64;
Δ = b2-4ac
Δ = -232-4·1·64
Δ = 273
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$X_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$X_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

$X_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-23)-\sqrt{273}}{2*1}=\frac{23-\sqrt{273}}{2} $
$X_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-23)+\sqrt{273}}{2*1}=\frac{23+\sqrt{273}}{2} $

See similar equations:

| 2(4x+2)=3x+9 | | 4x-(2x+4)=x-2 | | 4–7x=2–6x | | A)3x-(2x-1)=7 | | (3x-5)/2=-9 | | 13t+3t=5t | | t-(2t+5)-(1-2t)=(3+4t)-2(t-4 | | 4.2v-5-6.5= | | 70+70-7x=126 | | 3-z+3/10=3z-4/5+2z-15 | | -16=-4+5x | | y*4+3y*2=3 | | 9=-4y-6y-5 | | 11x-10=4x-52 | | 5(x+23)=180 | | 3(n+20)=2 | | 5x5=30 | | 3(x+28)=108 | | 4x+4=14x | | 8-2a-2= | | 2a+a=147 | | 6(3*y)=(6*3)*(6*y) | | q=43q= | | 2x-20=2x-40 | | G(2)=3x+3x-x+1 | | x-37=50 | | 2^x+1-9(x^2)+4=0 | | 4(x-2)x6=28 | | 32-x=7x-2 | | 8=(x/8) | | 6=(x/3) | | 8=1/2(1960)x^2 |

Equations solver categories